2019
DOI: 10.1016/j.ejrad.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the hanging protocol of Contrast Enhanced Mammography leads to similar diagnostic performance yet decreased reading times

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…18 While a previous review recommended that the LE images should be interpreted first, 12 a recent study reported that reviewing the recombined images first has similar diagnostic performance, while reading time is one-third faster. 21 Regardless of the order of image review, the interpretation of CEM exams must rely on reviewing both the LE views, which provide morphological information similar to conventional mammography, and the recombined images, which provide information about the vascularization of the lesion. 8(p12), [9][10][11][12]18 Currently, there is no dedicated Breast Imaging Reporting and Data System (BI-RADS) lexicon for CEM, but the mammographic and DCE-MRI descriptors of the BI-RADS lexicon can be easily adopted for use.…”
Section: Image Interpretation and Reportingmentioning
confidence: 99%
“…18 While a previous review recommended that the LE images should be interpreted first, 12 a recent study reported that reviewing the recombined images first has similar diagnostic performance, while reading time is one-third faster. 21 Regardless of the order of image review, the interpretation of CEM exams must rely on reviewing both the LE views, which provide morphological information similar to conventional mammography, and the recombined images, which provide information about the vascularization of the lesion. 8(p12), [9][10][11][12]18 Currently, there is no dedicated Breast Imaging Reporting and Data System (BI-RADS) lexicon for CEM, but the mammographic and DCE-MRI descriptors of the BI-RADS lexicon can be easily adopted for use.…”
Section: Image Interpretation and Reportingmentioning
confidence: 99%
“…Therefore, we do not agree with the bold statements published earlier by experts Mann and Velthuis 45 , which were based on the Pötsch review, stating that CEM would 'take us two steps back in breast imaging' compared to breast MRI. With such claims, we run the risk to prematurely exclude CEM from imaging, when in fact it is a modality which is increasingly being used with much potential 9 : more accessible to underserved populations, less expensive, shorter reading times and preferred by patients 4 , 17 , 18 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate this, Van Geel et al compared CEM diagnostic accuracy using the ‘standard’ hanging protocol and an inverse hanging protocol ( i.e., first interpret the recombined image, followed by the LE image). 28 They found that sensitivity and specificity were equivalent between standard and inverse protocols, 98 and 99 versus 94% and 90%, respectively, but that the inverse hanging protocol led to an average decrease in reading time of 6.2 s/case. This was mainly due to shorter LE image evaluation in the inverse hanging protocol, average recombined image evaluation time remained similar.…”
Section: Introductionmentioning
confidence: 97%
“…This was mainly due to shorter LE image evaluation in the inverse hanging protocol, average recombined image evaluation time remained similar. 28 Although time differences are small, they may become of interest in situations where large volumes of CEM examinations must be read, as is the case in screening programmes.…”
Section: Introductionmentioning
confidence: 99%